Understanding the Mandatory Language Policy for Immigrants and the Impact on Beur Cinema in France - Wulan Tri Astuti; Faruk Faruk; Budi Irawanto (Indonesian Association for Public Administration, 2021)
This article seeks to fill gaps in the literature regarding French cinema's treatment of immigration. Previous investigations of this theme have tended to position immigrants as objects, individuals perceived as creating problems, and as individuals using violence to resolve issues. This article highlighted in French films under a new genre, Beur Cinema, notably in the film Fatima This research discusses French cinema's depiction of immigrants' experiences with cultural negotiation mainly related to the French government's policy of Language Mandatory as one of the requirements for migrants to be granted citizenship. This article will also discuss the portrayal of the French government’s policy toward immigrants and how immigrants cope with the barriers and offer solutions to the problems in Beur cinema. The film Fatima, which was first published in 2015, will be analyzed by its cinematographic signs using the theory of cinematographic semiotics. This study finds that what has been understood as the cause of the lack of integration of immigrants is mainly that the residence permit is not justified. This research finds that the challenges of immigrants are also represented by difficulties in adapting to language skills, daily life routines, raising children, and even communicating with their diaspora community and the local residents.